Leveraging a faculty fellowship programme to develop leaders in interprofessional education. Issue 4 (3rd July 2016) - Robins, Lynne; Murphy, Nanci; Zierler, Brenda
Abstract: This article reports findings from an interprofessional education (IPE) study of a longitudinal faculty fellowship that aimed to develop IPE leaders at an academic institution based in the United States. Eight applicants were competitively selected to participate in an IPE track of the fellowship, alongside 14 faculty members who entered through a separate selection process. One year after graduation, a survey of the IPE fellows was undertaken to evaluate programme outcomes using open-ended questions based on an adaptation of Kirkpatrick's four-level training evaluation model. Results indicated that respondents valued participating in a longitudinal programme where they could learn about and practice teaching and leadership skills and conduct education scholarship. While learning on an interprofessional basis, the fellows reported establishing relationships that endured after graduation. This report suggests that adding IPE activities to existing faculty fellowship programmes can be an effective means of building faculty capacity to advance institutional IPE initiatives.